Impact of the Extended Family System and Access to Health Care Services in Kogi State, Nigeria - Attah, Philip Amana (NIU Journal of Social Sciences, 2023)
The extended family system is prevalent in Africa society particularly Nigeria and Kogi State. However, such extended relationship is posed to the challenge of accessing health care services. This paper is written to interrogating the extended family system and access to health care services in Kogi State, the work examines how the extended family system affects easy access to health care services in the State. The study adopts descriptive research design and the top-man sample size formular was adopted in determining the sample size from the infinite population. The frequency and percentage methods were adopted in data analysis and hypothesis tested using chi-square statistical technique. The study shows that the extended family system adversely affected access to health care services in Kogi State. Therefore, the study recommends that government should intervene through provision of adequate health care facilities in Kogi State Nigeria. Keywords: family, Extended family, health, care, services